Model Pembelajaran pada Kelas Anak Usia Dini di Era New Normal (Diniyah: Jurnal Pendidikan Dasar, 2023)
Through a holistic integrative approach and learning through play, Early Childhood Education (PAUD) develops six aspects of early childhood development. However, the pandemic has resulted in a shift in the learning process at schools. Students are directed to learn from their respective homes. This has led to the inability to carry out learning through play. This descriptive qualitative research aims to analyze the learning model applied in the new normal time using data collection techniques through observation, interviews, and documentation. The informants in this study are the school principal, school committee, six homeroom teachers, six parents of students, and sixteen students selected through snowball sampling determined by the researcher. This research was conducted for three months from April to June 2020. The results show that the forms of implementation of learning in the new normal are include WhatsApp groups, home visits, and a rolling system. The most effective result in learning in the new normal time is the rolling system, which divides students into several groups to avoid crowding.Keywords: Learning model, early childhood, new normal